2015
DOI: 10.1089/jwh.2014.4839
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive History and Chronic Hepatic Steatosis in the Michigan Study of Women's Health Across the Nation

Abstract: Background: Reproductive history, particularly maternal age at most recent birth, may reflect lower risk for chronic disease and mortality due to socioeconomic factors, lifestyle behaviors, or genetics. Reproductive history has not been examined with respect to hepatic steatosis, the most common liver disease in the United States. Our objective was to examine the association between reproductive history and hepatic steatosis. Methods: We examined the association between reproductive history characteristics-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…However, evidence of the relationship between AFB and hepatitis is scarce and inconsistent. Most relevant to this study is the one which suggested no signi cant association between AFB and hepatic steatosis among 331 women in Michigan, 20 but there was limited statistical power due to the small sample size. Besides that, there was another one conducted by Wang et al 21 Regrettably, they compared the risk of NAFLD between women who had given birth and nulliparous women only, and did not illustrate the differences in NAFLD risk between the different AFB categories.…”
Section: Discussionmentioning
confidence: 96%
“…However, evidence of the relationship between AFB and hepatitis is scarce and inconsistent. Most relevant to this study is the one which suggested no signi cant association between AFB and hepatic steatosis among 331 women in Michigan, 20 but there was limited statistical power due to the small sample size. Besides that, there was another one conducted by Wang et al 21 Regrettably, they compared the risk of NAFLD between women who had given birth and nulliparous women only, and did not illustrate the differences in NAFLD risk between the different AFB categories.…”
Section: Discussionmentioning
confidence: 96%